Use of bioethanol for sustainable electrical energy production (2009)
Nowadays, the climatic change has addressed the research targets to find renewable energy sources and in order to develop more efficient technologies in a simultaneous way, with the object of promoting a rational use of the energy in the frame of the sustainable development. In this case, an integrated process for sustainable electrical energy production from bioethanol was designed, taking advantage of hydrogen fuel as an energy carrier and fuel cells as efficient and clean devices. The calculated efficiency for this process is better than traditional power cycles, which constitutes a starting point for future developments of this technology.